2019
DOI: 10.1073/pnas.1821378116
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution limited-angle phase tomography of dense layered objects using deep neural networks

Abstract: We present a machine learning-based method for tomographic reconstruction of dense layered objects, with range of projection angles limited to ±10○. Whereas previous approaches to phase tomography generally require 2 steps, first to retrieve phase projections from intensity projections and then to perform tomographic reconstruction on the retrieved phase projections, in our work a physics-informed preprocessor followed by a deep neural network (DNN) conduct the 3-dimensional reconstruction directly from the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 65 publications
(78 reference statements)
1
73
0
Order By: Relevance
“…1). Unlike other recent works that propose to use supervised deep learning to aid in computational image reconstruction problems [35][36][37][38][39], including a number of works that rely on multi-angle illumination [30][31][32][40][41][42][43], the technique proposed here does not require any pre-training or dataset-specific assumptions. Instead, during iterative object reconstruction, DP-DT simply performs its optimization updates with respect to the parameters of a CNN, as opposed to directly updating the object voxels.…”
Section: Introductionmentioning
confidence: 99%
“…1). Unlike other recent works that propose to use supervised deep learning to aid in computational image reconstruction problems [35][36][37][38][39], including a number of works that rely on multi-angle illumination [30][31][32][40][41][42][43], the technique proposed here does not require any pre-training or dataset-specific assumptions. Instead, during iterative object reconstruction, DP-DT simply performs its optimization updates with respect to the parameters of a CNN, as opposed to directly updating the object voxels.…”
Section: Introductionmentioning
confidence: 99%
“…We modeled the Bessel beam as a constant line segment for computational simplicity, but models of the actual point spread function could be used for computing the inverse Radon transform. Approaches combining imaging physics and machine learning have been successfully applied in other tomography techniques for improving the reconstruction from sparse, shallow angle projections [13,[16][17][18][19][20]. Our networks were limited by GPU memory and therefore only low resolution images (128 pixel resolution instead of 512) were used.…”
Section: Discussionmentioning
confidence: 99%
“…Volume information is obtained from four independent projections recorded from four different angles using temporally multiplexed, tilted Bessel beams in a single frame scan. For volume reconstruction we combine inverse Radon transforms adapted for Bessel beam scanning with machine learning [13,[16][17][18][19][20]. Machine learning has been shown for example in optical phase imaging to allow high resolution reconstruction from sparse projections at shallow angles similar to the ones used here [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting alternative method for the inverse problem, also nonlinear, of reconstructing the three-dimensional (3D) refractive index distribution from intensity projections, is to define the DNN architecture according to the strong scattering model and store the refractive index values as weights of the DNN after training [44]. This "index-storing" DNN itself was subsequently used as Approximant to a traditional DNN for improving the estimates in 3D distributions with exceptionally small and highcontrast features or when the range of available angles of projec-tion is severely limited [45]. Extensive reviews of deep learning use for inverse problems can be found in [36,46,47].…”
Section: Introductionmentioning
confidence: 99%